2009
DOI: 10.1152/ajpgi.90551.2008
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide ameliorates intestinal barrier disruption associated withCitrobacter rodentium-induced colitis

Abstract: Attaching and effacing bacterial pathogens attach to the apical surface of epithelial cells and disrupt epithelial barrier function, increasing permeability and allowing luminal contents access to the underlying milieu. Previous in vitro studies demonstrated that the neuropeptide vasoactive intestinal peptide (VIP) regulates epithelial paracellular permeability, and the high concentrations and close proximity of VIP-containing nerve fibers to intestinal epithelial cells would support such a function in vivo. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 53 publications
5
57
0
1
Order By: Relevance
“…While the focus in our lab has remained on the ability of VNS to signal to EGCs, several studies have shown that enteric neurons may also be involved in maintaining intestinal epithelial barrier integrity. Studies by both Conlin, et al and Neunlist, et al have revealed the importance of the enteric neuron-secreted mediator, vasoactive intestinal peptide (VIP), which reduces intestinal barrier permeability and improves tight junction protein expression [26,27]. Given this data and the well-established connections between the Vagus nerve and the ENS, it is conceivable that VNS may also be directly innervating enteric neurons to secrete barrier-inducing mediators such as VIP.…”
Section: Discussionmentioning
confidence: 99%
“…While the focus in our lab has remained on the ability of VNS to signal to EGCs, several studies have shown that enteric neurons may also be involved in maintaining intestinal epithelial barrier integrity. Studies by both Conlin, et al and Neunlist, et al have revealed the importance of the enteric neuron-secreted mediator, vasoactive intestinal peptide (VIP), which reduces intestinal barrier permeability and improves tight junction protein expression [26,27]. Given this data and the well-established connections between the Vagus nerve and the ENS, it is conceivable that VNS may also be directly innervating enteric neurons to secrete barrier-inducing mediators such as VIP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent study, pharmacological reduction of intestinal permeability by blockage of tight junctions has been shown to attenuate intestinal inflammation in IL10−/− mice 3. Similarly, enhancement of IEB tight junction expression and resistance with vasoactive intestinal peptide4 reduced IEB lesions induced by pathogens such as Citrobacter rodentium 5…”
Section: Introductionmentioning
confidence: 96%
“…The fact that VIP inhibits the release of proinflammatory mediators by activated macrophages, promotes Th2 versus Th1 responses, and induces the generation of regulatory T cells (Tregs), suggested that its receptors may be targets for anti-inflammatory drugs. Accordingly, subsequent studies showed that VIP treatment inhibits ongoing inflammatory responses in murine models of septic shock, Crohn's disease, and rheumatoid arthritis (8)(9)(10)(11). However, the role of the endogenous peptide in maintaining the balance between potentially harmful and beneficial actions of the immune system remains to be elucidated.…”
mentioning
confidence: 99%